Pendampingan UMKM Kripik Paru Kidang Mas Salatiga Untuk Mendapatkan Surat Ketetapan Halal Sebagai Sarana Untuk Meningkatkan Citra Merek - wijayanti, sari (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2021)
Brand image creates value in a variety of ways, helps consumers to gain information, differentiate brands and create a positive impression. Due to the obligation from retailer, Kripik Paru Kidang Mas Salatiga as a small and medium sized enterprise seeks to add a logo halal and halal registration number to improve its brand image. Mentoring and education about halal food products and halal logo based on LPPOM MUI halal assurance system are needed. The result is Kripik Paru Kidang Mas Salatiga succeeded in obtaining a halal decree and adding a halal logo and halal registration number on its packaging.Keywords: sme;brand image;halal logo